Development of a Comprehensive Comparison Software for Automated Decision-Making in Impulse Testing of Power Transformers, Including a Review of Practices from Analog to Digital - Welson Bassi (Energies)
Power transformers are fundamental components in electrical grids, requiring robust insulation to operate reliably under various abnormal conditions, including overvoltages caused by lightning or switching. As defined by existing standards, the Basic Insulation Level (BIL) or Switching Insulation Level (SIL) of a transformer validates its reliability through impulse testing. These tests presume linearity in the overall system and equipment being tested. They compare waveforms at reduced and full impulse levels to detect or enhance insulation failures. Traditionally, this relies on visual inspection due to subjective acceptance criteria. This article presents a historical background review of the practices involving the use of analogue instruments evolved into digital oscilloscopes and digitizers, and the ways in which they enhance waveform acquisition and analysis capabilities. Despite advances in digital processing, including analyses on the frequency domain rather than only on time, such as transfer function analysis and coherence functions, and other signal transformations, such as wavelet calculation, interpreting differences in waveform records remains subjective. This article presents the development of a tool designed to emulate traditional photographic methods for waveform comparison. Moreover, the TRIMP software used enables multiple comparisons using various similarity and dissimilarity metrics in both the time and frequency domains, providing a robust system for identifying significant differences. The developed methodology and implemented metrics can form the basis for future machine learning or artificial intelligence (AI) applications. While digital tools offer significant advantages in impulse testing, improve reliability, reduce subjectivity, and provide robust decision-making metrics, their test approval remains based on visual comparisons due to consolidated engineering practices. Regardless of the metrics or indications obtained, the developed tool is a powerful graphic visualizer.